Gender dynamics in agricultural value chain development: Foundations and gaps - Pyburn, Rhiannon; Kruijssen, Froukje (Taylor and Francis, 2020)
Gender analysis exposes the uneven impact of global agricultural value chain development. This chapter traces an evolution in thinking over the past 20 years, recounting shifts, which are ongoing: from “women” to gender; from “women’s participation” to “gender equality;” from the initially siloed entry points of value chain performance and women, to convergence of the two; from a focus on tasks and roles to that of gender relations; from isolated “women’s projects” to gender integration throughout the chain; and from gender accommodative to gender-transformative interventions. Exploring gender dynamics has become more nuanced and sophisticated over time, but progress is non-linear and far from universal. This chapter reviews what we know about gender dynamics in agricultural value chains, including core concepts, frameworks, and tools. It looks at trends as well as the outcomes of gendered value chain interventions, and it concludes by pointing to outstanding gaps. The authors call for embracing a feminist lens in studying and engaging in agricultural value chain development. They advise explicit decision-making from practitioners and researchers in navigating inherent tradeoffs; between the often-competing objectives of value chain performance such as viability and efficiency, and those of gender equality, including the transformation of gender relations.